Application of Prony's Method for Stability Assessment of Converter-based Power Generation - Frauenknecht, Dominik; Schweinshaut, Bernd; Raab, Alexander; Mehlmann, Gert; Luther, Matthias; Wiest, Pascal; Heyde, Chris (IEEE Power and Energy Society General Meeting, 2024)
With the increasing integration of renewable energy sources and the associated changes in the dynamic behavior of the grid, new methods are needed to assess the power system stability. The application of the Prony method for the dynamic security assessment of converter-dominated grids is the new method presented in this paper. The mathematical principles of the classical Prony's method are outlined. Prony's method enables the decomposition of a signal into a series of complex exponential functions. The time-domain method allows the automated analysis of signal or measurement curves, with respect to damping, frequency, amplitude and phase offset of occuring oscillations. The approach is used to analyze the dynamic behavior of converter-based generation units. Based on electromagnetic transient (EMT) simulation results obtained from a high-voltage test system, the Prony method is applied to the fast control units of the converter. As a result, the frequency and damping characteristics of oscillations arising in converter controls are detected and used to assess power system stability by the newly defined Prony-based Oscillation Index (PBOI). The results indicate that the Prony method is applicable to detect and evaluate fast-interaction stability phenomena in converter-dominated power systems.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Converter-based Generation; Converter-dominated Power Systems; Dynamic Security Assessment (DSA); Electromagnetic Transient (EMT) Simulation; Modular Multilevel Converter (MMC); Prony's Method